2020
DOI: 10.1088/1361-6463/abc11b
|View full text |Cite
|
Sign up to set email alerts
|

Driving frequency effect on discharge parameters and higher harmonic generation in capacitive discharges at constant power densities

Abstract: Very high frequency (VHF) driven capacitive discharges are now being increasingly adopted for plasma-based materials processing due to their high processing rates and lower substrate damage. Past studies related to complex plasma dynamics and higher harmonics generation in such systems were limited to constant voltage/current conditions, whereas, industrial systems are mostly driven by constant power density sources. In the present study, using particle-in-cell (PIC) simulation, we explore the dynamics of coll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…During these interactions, the instantaneous sheath edge position is modulated with highfrequency oscillations. Similar effects have been observed in capacitive discharges operating at a very high frequency [9][10][13][14]70]. These multiple ionization beams support higher plasma density in the discharge that is observed at N = 12.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…During these interactions, the instantaneous sheath edge position is modulated with highfrequency oscillations. Similar effects have been observed in capacitive discharges operating at a very high frequency [9][10][13][14]70]. These multiple ionization beams support higher plasma density in the discharge that is observed at N = 12.…”
Section: Resultssupporting
confidence: 80%
“…As shown in figure 9, the energy spread in the bi-modal energy peaks (E) is decreasing with an increase in the value of N. For the current chosen range (N = 2 -12), the value of E is decreased from 34 eV to 17 eV i.e., a 50% drop in the energy spread is observed. A decrease in the value of E is on the one hand due to an increase of high-frequency content in the driving waveform that drives IEDF from a bi-modal shape to a narrow distribution as observed in the very high frequency CCP discharges [10]. The high-frequency component on the instantaneous sheath edge position is clearly observed as shown in figure 6 (d).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…For the present study, we have used a well-tested and benchmarked 1D3V, electrostatic, selfconsistent, PIC code 32,33 . The code has been used extensively in previous studies and details can be found in the literatures [34][35][36][37][38][39][40][41][42][43][44][45][46] . As an input, a current waveform is chosen given by the following mathematical expression:…”
Section: Simulation Technique and Parametersmentioning
confidence: 99%